Periodic characterization of alkylnaphthalenes in stack gas and ambient air around a medical waste incinerator - Adesina, Olusola Adedayo; Sonibare, Jacob Ademola; Diagboya, Paul N.; Adejuwon, Adesuji; Famubode, Temitope; Bello, Josiah O. (Springer-Verlag GmbH Germany, 2023)
Environment Science Pollution Research